2009
DOI: 10.1007/s11426-009-0115-y
|View full text |Cite
|
Sign up to set email alerts
|

Chiral assembly of achiral pseudoisocyanine with D- and L-phenylalanine

Abstract: Supramolecular chirality and molecular self-assembly are important and interesting phenomena in living and non-living systems. In this work, supramolecular chirality of achiral pseudoisocyanine (PIC) J-aggregates was successfully induced by D-, L-phenylalanine (Phe) and other amino acids in NaCl solution. The chiral J-aggregates showed a characteristic, induced circular dichroism (ICD) in the visible region of J-band chromophore which depends on the absolute configuration, concentration and side groups of α-am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 41 publications
0
14
2
Order By: Relevance
“…55 In this work, the ICD signals of the PAAS-PIC J-aggregates at 560 nm, 532 nm and 499 nm of the optically active PIC J-aggregates that was formed in the anionic polyelectrolyte do not reversed. Moreover, the CD intensity does not show too much change.…”
Section: Chirality Memorization In the Pic-paas J-aggreagatesmentioning
confidence: 66%
See 1 more Smart Citation
“…55 In this work, the ICD signals of the PAAS-PIC J-aggregates at 560 nm, 532 nm and 499 nm of the optically active PIC J-aggregates that was formed in the anionic polyelectrolyte do not reversed. Moreover, the CD intensity does not show too much change.…”
Section: Chirality Memorization In the Pic-paas J-aggreagatesmentioning
confidence: 66%
“…48,49 The induced optical activity of cyanine dye J-aggregates have been achieved by the induction of large biopolymers such as proteins, 50,51 oligopeptides, 52 polysaccharids, 53 DNA, 54 and small molecules such as amino acids. 55 However, one basic question is still open: exactly how the weak non-covalent interaction among the local chirality of a small molecule translates to global helicity of preferred handedness in supermolecules still remains to be elucidated.…”
Section: Introductionsmentioning
confidence: 99%
“…He et al 36 established a chirality-sensing system based on pseudoisocyanine (PIC, 38) aggregates. Achiral PIC 38 is known to form J-type aggregates, with its critical aggregation concentration in water tuneable by salt concentration.…”
Section: Supramolecular Polymersmentioning
confidence: 99%
“…A number of researchers have revealed that some small achiral molecules can form chiral nano/micro-structures by host-guest and guest-guest interactions. [28][29][30][31][32][33][34][35][36][37][38][39][40] The driving force for the formation of chiral supermolecules is generally constructed on the non-covalent interactions, such as van der Waals interactions, hydrogen bonds, p-p stacking, metal coordination, electrostatic interaction and hydrophobic interactions.…”
Section: Introductionmentioning
confidence: 99%